Lay understandings of drug‐gene interactions: The right medication, the right dose, at the right time, but what are the right words? - Karen M. Meagher; Kelsey Stuttgen Finn; Susan H. Curtis; Jack Borucki; Annika T. Beck; Amal W. Cheema; Richard R. Sharp (Wiley, 2022)
Abstract As pharmacogenomic (PGx) testing increases in popularity, lay concepts of drug‐gene interactions set the stage for shared decision making in precision medicine. Few studies explore what recipients of PGx results think is happening in their bodies when a drug‐gene interaction is discovered. To characterize biobank participants' understanding of PGx research results, we conducted a focus group study, which took place after PGx variants conferring increased risk of dihydropyrimidine dehydrogenase (DPD) deficiency were disclosed to biobank contributors. DPD deficiency confers an increased risk of adverse reaction to commonly used cancer chemotherapeutics. Ten focus groups were conducted, ranging from two to eight participants. Fifty‐four individuals participated in focus groups. A framework approach was used for descriptive and explanatory analysis. Descriptive themes included participants' efforts to make sense of PGx findings as they related to: (1) health implications, (2) drugs, and (3) genetics. Explanatory analysis supplied a functional framework of how participant word choices can perform different purposes in PGx communication. Results bear three main implications for PGx research‐related disclosure. First, participants' use of various terms suggest participants generally understanding their PGx results, including how positive PGx results differ from positive disease susceptibility genetic results. Second, PGx disclosure in biobanking can involve participant conflation of drug‐gene interactions with allergies or other types of medical reactions. Third, the functional framework suggests a need to move beyond a deficit model of genetic literacy in PGx communication. Together, findings provide an initial evidence base for supporting bidirectional expert‐recipient PGx results communication.